2023
DOI: 10.1186/s43020-023-00104-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of GNSS zenith tropospheric delay responses to atmospheric variables derived from ERA5 data over Nigeria

Abstract: Tropospheric delay is a major error caused by atmospheric refraction in Global Navigation Satellite System (GNSS) positioning. The study evaluates the potential of the European Centre for Medium-range Weather Forecast (ECMWF) Reanalysis 5 (ERA5) atmospheric variables in estimating the Zenith Tropospheric Delay (ZTD). Linear regression models (LRM) are applied to estimate ZTD with the ERA5 atmospheric variables. The ZTD are also estimated using standard ZTD models based on ERA5 and Global Pressure and Temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…It provides real-time and high-precision deformations, facilitating effective analysis and predictions. However, the complex environment around hydraulic structures leads to measurement errors, such as atmospheric delays [11][12][13] and multipath effects [14][15][16][17]. These errors are difficult to process, which adds obstacles to the prediction Appl.…”
Section: Introductionmentioning
confidence: 99%
“…It provides real-time and high-precision deformations, facilitating effective analysis and predictions. However, the complex environment around hydraulic structures leads to measurement errors, such as atmospheric delays [11][12][13] and multipath effects [14][15][16][17]. These errors are difficult to process, which adds obstacles to the prediction Appl.…”
Section: Introductionmentioning
confidence: 99%
“…With an average of root mean squares error of roughly 12 mm, the ZTD showed great agreement with IGS products. Nzelibe et al [27] proved a great improvement in accuracy in ZTD estimation for GNSS positioning when using the ERA5 atmospheric variables. Zhang et al [28] proposed a method to obtain better ZHD corrections to solve the issues with the application of the conventional approach in areas with high variations in height, and their results showed that the method can achieve an improvement in accuracy of 50% over the conventional approach.…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous improvement of these meteorological empirical models, some scholars have combined meteorological empirical models with zenith tropospheric delay models, such as the GPT3 + Saastamoinen method, which calculates the average deviation of ZTD at more than 16,000 global stations over 10 years at around −0.99 cm [26]. At present, some scholars have also combined numerical reanalysis data with tropospheric delay models and have achieved good results in improving the accuracy of prior values in precise models and in improving the positioning accuracy as well [7,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%